Association Analysis of Dietary Inflammatory Index and Gestational Diabetes Mellitus: Based on National Health and Nutrition Examination Survey Database - Zeng, Yamin; Piao, Yina (Experimental and Clinical Endocrinology & Diabetes, 2024)
Objective This study focused on the association of the Dietary Inflammatory Index (DII) with the risk of gestational diabetes mellitus (GDM) using data from the National Health and Nutrition Examination Survey (NHANES).Methods Data from two cycles of NHANES (2007–2010) were analyzed. Weighted logistic regression models were constructed to explore the relationship between DII and GDM. Stratified and subgroup analyses with adjustment for confounding factors were carried out to explore the association between DII and GDM. Mediation analysis was conducted to investigate potential mediating factors.Results A total of 1,421 samples were analyzed. Based on the weighted logistic regression model, a strong positive association was observed between DII score and GDM risk (OR: 1.14, 95%CI: 1.02–1.26, P<0.01), suggesting that a pro-inflammatory diet could considerably increase the likelihood of GDM occurrence. This positive association was particularly significant in populations who consume alcohol (OR:1.17, 95%CI: 1.03–1.34, P<0.01) and have a body mass index>30 kg/m² (OR: 1.18, 95% CI: 1.01–1.38, P<0.05). Mediation analysis indicated that the white blood cell count mediated the association between DII and GDM, with an indirect effect of 0.000828 (95% CI: 0.000226–0.001347, P=0.001) and a mediation proportion of 8.01%. Specifically, the neutrophil count as a component contributed to this mediation effect (0.000774, 95% CI: 0.00014–0.001063, P=0.001), with a mediation proportion of 7.59%.Conclusion A pro-inflammatory diet in women elevates the likelihood of GDM occurrence. An anti-inflammatory dietary pattern may be a protective intervention for GDM.
Keywords: gestational diabetes mellitus; dietary inflammatory index; neutrophil count; cross-sectional study; National Health and Nutrition Examination Survey